Emerging Patterns of Innovation in Pharmaceutical Manufacturing in India: Expectations from Liberalization and Implications for Industrial Upgrading - John, R. (H. : ĐHKT, 2020)
The Indian Pharmaceutical Industry is one of the growing industries in India, accounting for 3.1 to 3.6% of global industry in value terms as well as 10% in volume terms. India exported pharma products worth Rupees 411.3 billion (US $ 6.4 billion) during April-September 2017. India has 10,500 manufacturing units and over 3000 companies. India has the largest number of USFDA approved manufacturing units outside United States. India’s cost of production is nearly 33 % lower than that of the US; Labour costs 50-55 per cent cheaper than in US and EU. The cost of setting up a production plant is 40 per cent lower than in US and EU.